Synthesis and Applications of Isoindoline Monomethine Disperse Dyes - Sekar, N.; Rajule, R.N. (Asian Journal of Chemistry, 2010)
Monomethine styryl dyes have been synthesized by reacting 1-amino-3-imino isoindoline first with active methylene compound in presence of base followed by reaction with electronrich aromatic compounds in acetic anhydride and catalytic amount of sulphuric acid. The dyes are evaluated on polyester fabric.